2006
DOI: 10.1016/j.brainres.2006.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic hyperinnervation and inflammatory cell NGF synthesis following myocardial infarction in rats

Abstract: Sympathetic hyperinnervation occurs in human ventricular tissue after myocardial infarction and may contribute to arrhythmias. Aberrant sympathetic sprouting is associated with elevated nerve growth factor (NGF) in many contexts, including ventricular hyperinnervation. However, it is unclear whether cardiomyocytes or other cell types are responsible for increased NGF synthesis. In this study, left coronary arteries were ligated and ventricular tissue examined in rats 1-28 days post-infarction. Infarct and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
140
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 43 publications
12
140
1
Order By: Relevance
“…In addition, the up-regulated NGF expression was associated with the increase in TNF-␣ and IL-1␤ at the atrium, indicating that inflammation could have induced the NGF expression to promote a higher density of GAP-43-and TH-positive staining nerves. Thus our data support the concept that NGF expression plays a key role in modulating the autonomic remodeling process (11,26). In addition, we showed that oxidative stress, as evidenced by increased superoxide and MDA generation, was involved in the post-MI remodeling process, and decreases in oxidative stress are also observed with simvastatin therapy.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the up-regulated NGF expression was associated with the increase in TNF-␣ and IL-1␤ at the atrium, indicating that inflammation could have induced the NGF expression to promote a higher density of GAP-43-and TH-positive staining nerves. Thus our data support the concept that NGF expression plays a key role in modulating the autonomic remodeling process (11,26). In addition, we showed that oxidative stress, as evidenced by increased superoxide and MDA generation, was involved in the post-MI remodeling process, and decreases in oxidative stress are also observed with simvastatin therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Results presented here extend the pathological actions of proNGF to include induction of vascular injury after MI in humans and cardiac I-R injury in mice. The coordinate up-regulation of proNGF and p75 NTR within 24 h after I-R injury (Hiltunen et al, 2001;Hasan et al, 2006; this paper) is consistent with the rapid induction observed in the central nervous system. The progressive decrease in cardiac contractility in proNgf-HA/ + mice, but not Ngf +/ mice, indicates that sustained levels of proNGF, rather than haploinsufficiency of mature NGF, induces cardiac microvascular dysfunction.…”
Section: P75 Ntr Deficiency Provides Protection From Infarct Expansionsupporting
confidence: 86%
“…Acute inflammatory states such as myocardial infarction (Hasan et al, 2006), ozone-induced pulmonary inflammation (Graham et al, 2001), interstitial cystitis (Peeker et al, 2000), and intestinal parasitic infection (Kannan et al, 1996) increase sympathetic innervation density in the afflicted tissues. Chronic autoimmune diseases are also associated with remodeling of sympathetic axons; recent studies of inflammatory bowel disease (IBD) patients and animal models of IBD provided anatomical evidence of increased sympathetic innervation of colonic smooth muscle (Lourenssen et al, 2005), mesenteric blood vessels (Birch et al, 2008), and dorsal root ganglia (Xia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of sympathetic axonal sprouting following myocardial infarction, for example, is positively correlated with the degree of infiltrating immune cells, which synthesize and secrete proinflammatory cytokines (Hasan et al, 2006;Wernli et al, 2009). , the principal cytokine secreted from the novel T H 17 lineage of helper T lymphocytes, has recently emerged as a key proinflammatory cytokine that orchestrates immune responses during infection, acute inflammation, allergy, and autoimmune disease (Nakae et al, 2003;Bettelli et al, 2007;Korn et al, 2007;Oboki et al, 2008;Littman and Rudensky, 2010).…”
Section: Introductionmentioning
confidence: 99%